High pressure processing of fruit and vegetable juices - Houška, Milan; Silva, Filipa Vinagre Marques da (CRC Press, 2017)
"High pressure processing in one of the fastest growing food processing technologies, retaining almost all the nutrients and health benefits found in the original raw fruit or vegetable. This book reviews and summarizes the latest advances in the novel highpressure processing technique for preserving fruits, fruit juices and their mixtures. It will contain basic information on the relation of process parameters high-pressure treatment and safety and quality of fruit and vegetable juice products. The book focuses on juice quality parameters, nutritional values and bio-active health components, and microbial safety."--Provided by publisher
Keywords: Fruit processing plants.; Fruit juices.; High pressure (Technology); High pressure (Science); elektronické knihy; electronic books